Downward nominal wage rigidity in the OECD - Steinar Holden; Fredrik Wulfsberg (University of Oslo, Department of Economics, 2005)
This paper explores the existence of downward nominal wage rigidity (DNWR) in 19 OECD countries, over the period 1973–1999, using data for hourly nominal wages at industry level. Based on a novel nonparametric statistical method, which allows for country and year specific variation in both the median and the dispersion of industry wage changes, we reject the hypothesis of no DNWR. The fraction of wage cuts prevented due to DNWR has fallen over time, from 70 percent in the 1970s to 11 percent in the late 1990s, but the number of industries affected by DNWR has increased. DNWR is more prevalent when inflation is high,unemployment is low, union density is high and employment protection legislation is strict.
Keywords: C14; C15; E31; 330; Downward nominal wage rigidity; OECD; employment protection legislation; wage setting; Lohnrigidität; Arbeitsmarktflexibilisierung; Schätzung; OECD-Staaten